STATE-PRIVATE PARTNERSHIP − A MODEL FOR REFORMING UNIVERSITY CLINICS - Chopchik, Vitaliy (The Ukrainian Scientific Medical Youth Journal, 2019)
The aim of the work to substantiate the possibility of using public-private part- nership (PPP) as a tool for the innovative development of university clinics (UK).Results the article reveals the problems of the current system of university clinics, shows the foreign experience of using public-private partnerships in healthcare. PPP mechanism is defined as the main tool for reforming university clinics. The main directions of the devel- opment of the UK, such as: regulatory, organizational, managerial, financial, informational, capable of providing a modern, autonomous, economically sustainable model of the UK, is also presented in the article.Conclusions the article describes the current university clinics in Ukraine. Taking into account the experience of developed countries of the world, as well as the economic situation in Ukraine, a more effective form of organizing of UK on the principles of PPP as a tool for innovative development of university clinics is sustained.